Growing Capsicum, tomato and cucumber through stem cuttings - Kumar, Pardeep; Sharma, Parveen; Raj, Desh; Negi, Viplove; Rana, Shivani; Vats, Binny (Indian Horticulture, 2019)
Vegetative propagation is quite common in a few vegetable crops like garlic, ginger, colocasia, potato, turmeric, elephant-foot yam etc. where the most common method of vegetative propagation, i.e. pieces of corm/bulb/tuber/ stem has been practised. Capsicum, tomato and cucumber are three principle money-spinner crops grown at commercial scale under protected conditions. The major issue related to these crops is the availability of seed of desired hybrids or varieties to be grown. Public sector hybrids for protected cultivation are scanty and not available to the polyhouse growers, whereas private sector hybrids are costly and sometimes not available to the growers. Every year, area under protected cultivation is increasing and farmers are facing problem of quality planting material. Moreover, there are a few identified hybrids or varieties which perform well under protected environments, thereby limiting the choice of growers to grow varieties or hybrids available in the market. The new technology of vegetative propagation in Capsicum, tomato and cucumber through stem cuttings can be the best alternative to growers. The Department of Vegetable Science and Floriculture, CSK HPKV-Palampur, is pioneer in developing a stem cutting propagation technology in Capsicum, tomato and cucumber which can be easily adopted by farmers for multiplication of promising planting material.